Analisis Nilai-Nilai Moral Pada Film Animasi Finding Nemo dan Relevansinya Pendidikan Sekolah Dasar - Dian Maharani Ambar Pradini; Sukamto; Intan Rahmawati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The purpose of this research is (1) to describe and determine the moral values in the film "Finding Nemo", (2) to explain the relevance of the moral values contained in the film "Finding Nemo" to character education for elementary level students. in the film "Finding Nemo". And also, its relevance to character education. Meanwhile, the data analysis technique uses content analysis. Based on data analysis, it was found that (1). The moral values contained in the film "Finding Nemo" include: a) parents' love for their children, b) obedience to parents, c) trying hard, d) parents must give freedom to their children, e) help between each other, f) trust each other between friends and family, g) never be embarrassed to apologize, h) be ready to let your child go on an adventure, i) learn to work together. (2). The relevance of the moral values contained in the film "Finding Nemo" to character education for elementary level students is found in the character values of hard work, creativity, independence, curiosity, friendship/communicativeness, love of peace, social care and responsibility.